1997
DOI: 10.1093/humrep/12.5.967
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of 7alpha-methyl-19- nortestosterone after intramuscular administration in healthy men

Abstract: 7alpha-Methyl-19-nortestosterone (MENT) is a potent synthetic androgen that is resistant to 5alpha-reductases and therefore less prone to over-stimulate the prostate. It is a good candidate for implant administration in long-term androgen replacement therapy for hypogonadal men or as part of a male contraceptive system. To investigate the pharmacokinetics of MENT after i.m. administration, single i.m. injections of 2, 4 or 8 mg of micronized MENT were given in aqueous suspension to 18 healthy men in two clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…7␣-Methyl-19-nortestosterone (MENT) is a synthetic androgen that is more potent than T for gonadotropin suppression and is resistant to 5␣-reduction, with potential advantages when used as a contraceptive (15)(16)(17). MENT acetate (Ac) has diffusion characteristics that are well suited for delivery via subdermal implants.…”
mentioning
confidence: 99%
“…7␣-Methyl-19-nortestosterone (MENT) is a synthetic androgen that is more potent than T for gonadotropin suppression and is resistant to 5␣-reduction, with potential advantages when used as a contraceptive (15)(16)(17). MENT acetate (Ac) has diffusion characteristics that are well suited for delivery via subdermal implants.…”
mentioning
confidence: 99%
“…In a study in castrated monkeys, MENT showed a 10-fold greater potency (vs. testosterone) for LH inhibition, but only 2-fold greater potency at stimulating prostate growth (295). In men, MENT has a short half-life, probably due to the fact that MENT does not appear to bind to SHBG (296). Therefore, MENT implants have been synthesized to allow for sustained delivery.…”
Section: H Selective Androgen Receptor Modulators For Male Contracepmentioning
confidence: 99%
“…Initial data showed relatively good efficacy, but typical testosteronerelated side effects. Suvisaari et al 53 and others have shown that MENT has a short half-life and is not suitable for long-term injection and does not show significant FSH suppression. Dimethandrolone undecanoate is another potent synthetic androgen with some progestational activity that represents an orally active substance that appears to suppress LH levels in vitro and in rabbit models.…”
Section: Testosterone Alonementioning
confidence: 99%